2007
DOI: 10.1111/j.1747-0765.2007.00175.x
|View full text |Cite
|
Sign up to set email alerts
|

Free oxides and short-range ordered mineral properties of brown forest soils developed from different parent materials in the submontane zone of the Kanto and Chubu districts, Japan

Abstract: The general chemical properties of Brown Forest Soils (BFS) differ according to the nature of their parent materials. The influence of volcanic ash as a soil parent material must be regarded as a factor producing differences in the submontane zone of the Kanto and Chubu districts in Japan. To determine the influence of volcanic ash, the free oxides and short-range ordered mineral compositions of these soils were examined. Brown Forest Soils, excluding the soils derived from volcanic ash in these regions, had c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…The predominant soil group is brown forest soil, which covers 70% of the forest sector and has a carbon stock of 87 Mg C ha −1 (Table 5). Japanese brown forest soils are often strongly influenced by volcanic ash (Imaya et al. 2007) and are classified as Andisols in some cases (Soil Survey Staff 2006), but the mean value of all soil groups (90 Mg C ha −1 ) is not as high as we expected and is similar to the value (88 Mg C ha −1 ) indicated in the IPCC guidelines (IPCC 2006).…”
Section: Dead Organic Matter and Soil Carbon Stocksupporting
confidence: 65%
“…The predominant soil group is brown forest soil, which covers 70% of the forest sector and has a carbon stock of 87 Mg C ha −1 (Table 5). Japanese brown forest soils are often strongly influenced by volcanic ash (Imaya et al. 2007) and are classified as Andisols in some cases (Soil Survey Staff 2006), but the mean value of all soil groups (90 Mg C ha −1 ) is not as high as we expected and is similar to the value (88 Mg C ha −1 ) indicated in the IPCC guidelines (IPCC 2006).…”
Section: Dead Organic Matter and Soil Carbon Stocksupporting
confidence: 65%
“…The concentrations of Al and Fe extracted by KCl showed quite low values. The data obtained by a citrate dithionite solution, which can estimate nearly all secondary oxides and organic complexes in soils, also showed low values of Al and Fe as compared with data for various types of soil in central Japan (2.7-28.9 g kg -1 for Al, and 8.1-46.4 g kg -1 for Fe, respectively) (Imaya et al 2007). Consequently, the soil at Mt.…”
Section: Discussionmentioning
confidence: 94%
“…Volcanic ash soil contains large amounts of aluminum (Al) and iron (Fe) (Bautista and Inoue 1993;Imaya et al 2007; Kayama et al 2011). When plants absorb Al, the cell division of roots and the uptake of various nutrients are inhibited (Marschner 1995;Kochian et al 2004;Yang et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Takahashi et al (2001) showed that non-allophanic Andosols in several forest soils of Aomori and Akita Prefectures were formed in Pleiocene sedimentary rocks and Miocene green tuff mixed by landslides with no evidence of tephra deposition. Recent studies in forested areas in Japan indicate widespread distribution of non-allophanic Andosols mixed with Brown forest soils (Imaya et al, 2005(Imaya et al, , 2007(Imaya et al, , 2010a.…”
Section: Formation Of Al-humus Complexesmentioning
confidence: 99%